2015
DOI: 10.1140/epjp/i2015-15202-6
|View full text |Cite
|
Sign up to set email alerts
|

Local mechanical properties of bladder cancer cells measured by AFM as a signature of metastatic potential

Abstract: Abstract. The rheological properties of bladder cancer cells of different invasivities have been investigated using a microrheological technique well adapted in the range [1-300 Hz] of interest to understand local changes in the cytoskeleton microstructure, in particular actin fibres. Drugs disrupting actin and actomyosin functions were used to study the resistance of such cancer cells. Results on a variety of cell lines were fitted with a model revealing the importance of two parameters, the elastic shear pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 52 publications
5
56
1
1
Order By: Relevance
“…In our study, by using AFM to analyze cell membrane biomechanical properties, we found that cell elasticity was significantly altered with the treatment of 30μM Y-27632 as the Young's modulus of treatment group showing significant upregulation. Consistently, Abidine et al ., also found that Y-27632 increased the plateau modulus of bladder cancer cell [ 46 ]. Recently, growing evidence suggests that the mechanical properties of the cell are closely related to cell proliferation, apoptosis, migration and adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, by using AFM to analyze cell membrane biomechanical properties, we found that cell elasticity was significantly altered with the treatment of 30μM Y-27632 as the Young's modulus of treatment group showing significant upregulation. Consistently, Abidine et al ., also found that Y-27632 increased the plateau modulus of bladder cancer cell [ 46 ]. Recently, growing evidence suggests that the mechanical properties of the cell are closely related to cell proliferation, apoptosis, migration and adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al, 2009;Mandal et al, 2016). Fibroblasts (Thoumine & Ott, 1997a;Wottawah et al, 2005;Park et al, 2005), hepatoma cell lines (Zhang et al, 2002), prostate cancer cells (Faria et al, 2008), kidney cell lines (Rebelo et al, 2013), glioma cells (Pogoda et al, 2014) and bladder cancer cells (Bertseva et al, 2012;Lekka et al, 1999;Abidine et al, 2015) have also been studied. Cell lines from patients with primary oral or thyroid cancer were used for the first time to our knowledge by Remmerbach et al (2009) and Prabhune et al (2012), respectively.…”
Section: Mechanics Of Normal Cells Versus Cancer Cells From the Same mentioning
confidence: 99%
“…Liu et al, reported that bladder cancer cell at higher grades possess larger SMC values and lower Young's modulus than cancer cells at lower grades, by using two independent techniques of microfluidic and atomic force microscope (AFM) to measure RT4 and T24 cells [28]. Abidine et al, also observed that cellular elastic modulus is associated with cells' invasion ability by measuring the elastic modulus of RT112, T24, and J82 cells using AFM [29]. However, these studies only measured either mechanical or electrical properties of cells due to the limits of the adopted tools.…”
Section: Introductionmentioning
confidence: 99%